PENGARUH KUALITAS LAYANAN MOBILE APPLICATION TRAVELOKA TERHADAP KEPUASAN PELANGGAN PADA KOMUNITAS BACKPACKER DUNIA - Ardi, Venny Destasia; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Service quality is an important factor in the formation of customer satisfaction. This study explain how the influence of the quality of services provided by traveloka through the medium that mobile application. Following indicator of service quality using model e-servqual to be tested, covering efficiency, reliability, fulfillment, privacy, responsiveness, compensation, and contact. Used to see how big the influence of the customer satisfaction, indicator include the suitability of hope, interest been back, and willingness recommend. Theory used in this study is theory S-R. The purpose of this study is to find out how big the influence of the quality of mobile application traveloka to the customer satisfaction in the community backpacker the world. This research uses explanative quantitative research method with data collection technique that is distributing questionnaires to 96 respondents in the group of active world backpacker group, with accidental sampling technique that is choosing anyone who happened to be found to be sampled. And the technique of data analysis in this research using simple linear regression analysis technique. The results of this study indicate that the value of regression coefficients in this study is y 1.880 + 0.269 x the number of constants (a) of 1.880 and the coefficient of variable xsebesar 0.269. Meanwhile t count 11,198 bigger when compared with t table equal to 1,246, with significance level 0.000 less than a 0,05. Based on the statistical calculations obtained, the hypothesis for this research is ha there is influence between service quality (x) to satisfaction subscriptions (y). Then it means ha accepted ho rejected. Based on the table "model summary" shows that the value of r 0.756 and the coefficient of determination (r quare) is 0.572 result of the correlation coefficient correlation 0.756 x 0.756. This figure shows the understanding that contribution of variable of service quality (x) to customer satisfaction (y) is 57,2% with medium category. While the rest of 42.8% influenced by other variables not included in this study. Key Word: Service Quality, Customer Satisfaction, Theory S-R,E-servqual model